Risks and Protective Factors of Hispanic Families and Their Young Children during the COVID-19 Pandemic - Natasha Cabrera; Minxuan He; Yu Chen; Stephanie M. Reich (MDPI AG, 2022)
This study examines the risk-related factors during the pandemic and protective factors that might reduce its effects on family functioning in a sample of 161 low-income Hispanic parents in the United States, recruited from an ongoing longitudinal intervention study. They were surveyed about family functioning six months into the pandemic. We focused on the associations between social (e.g., exposure to the virus) and economic (e.g., job loss) pandemic-related risks on parental stress, parenting, and children's socioemotional problems and skills, as well as the degree to which coparenting support, parents' positivity, economic support, and access to services and information mitigated (protected) the negative effects of these stressors on family functioning. We found that increases in economic risk were associated with more child competence skills, whereas increases in social risk were associated with less parental engagement. Positivity and economic support moderated the effects of economic risk on parental stress and engagement. These findings show that to intervene effectively with low-income Hispanic families, we need to strengthen and support the resources for coping with adversity.